Review of the genus Apterolarnaca Gorochov (Orthoptera: Gryllacrididae) with proposal of a new synonym and description two new species - Xun, Bian; Rong-Sheng, Lu; Fuming, Shi (Zootaxa, 2016)
Apterolarnaca ovala Bian & Shi, 2015 is proposed as a synonym of Apotrechus truncatolobus Li & Liu, 2015 and transfers the species to the genus Apterolarnaca Gorochov, 2004. Meanwhile, based on the collection of the Museum of Hebei University, two new Chinese species of Apterolarnaca are described, Apterolarnaca nigrifrontis Bian & Shi sp. nov. and Apterolarnaca quadrimaculata Bian & Shi sp. nov..